Comments on the Draft Environmental Assessment/Environmental Impact Report for Land Acquisition and Airport Development at Oxnard Airport-SCAG No. I 9800601 - Arnold Sherwood:::::: (1998)
Detailed comments from the Southern California Association of Governments regarding the environmental report on developments being made at the Oxnard Airport.